2018
DOI: 10.1093/biolinnean/bly057
|View full text |Cite
|
Sign up to set email alerts
|

Is sexual brutality maladaptive under high population density?

Abstract: Coercive copulation is frequent in promiscuous mating systems, generating both benefits (e.g. higher copulation rate) and costs (e.g. injuries and fewer foraging opportunities). The negative consequences of sexual harassment are expected to increase with increasing population density with male-biased operational sex ratio (OSR). This study offers an example in which the frequency and severity of the injuries inflicted on female tortoises during forced copulations increased with population density and biased OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Male traits that facilitate coercive matings have the potential to harm females [4]. Indeed, male-induced injury has been documented in a wide range of taxa, including mammals [4,47], birds [49], reptiles [35,50,51], insects [29,30,34,37,38] and molluscs [31,52]. Harmful coercion also occurs in sexual cannibals, but is rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male traits that facilitate coercive matings have the potential to harm females [4]. Indeed, male-induced injury has been documented in a wide range of taxa, including mammals [4,47], birds [49], reptiles [35,50,51], insects [29,30,34,37,38] and molluscs [31,52]. Harmful coercion also occurs in sexual cannibals, but is rare.…”
Section: Discussionmentioning
confidence: 99%
“…[ [29][30][31][32][33][34][35][36][37][38][39] or a result of selection favouring the harmful trait in an unrelated context [1,40].…”
Section: Introductionmentioning
confidence: 99%
“…Social stress associated with high densities probably reflects both increased predation pressure and competition for food, basking and oviposition sites (Pechenik, 2006). For adult females, high densities also reflect more intense mating harassment overall (Golubović et al, 2018). Van Gossum et al (2001 found that mating harassment rates, and particularly the tendency of males to target common female morphotypes, increased at high population densities, suggesting that common morphs, and particularly gynochromes (Rivera & Sánchez-Guillén, 2007), will be most prone to experiencing the cold tolerance benefit of density-induced social stress.…”
Section: Discussionmentioning
confidence: 99%
“…From 2008 until 2019, we studied the ecology and morphology of tortoises in two dense populations (> 20 adults / ha) of T. hermanni in two nearby sites (~4.5 km away from each other) of the Prespa Lake region in North Macedonia: Golem Grad Island (GG, ~18 ha; N 40°52'; E 20°59'), and Konjsko village (KV, ~20 ha, N 40°54'; E 20°99') (Djordjević et al, 2011;Arsovski et al, 2018a;Golubović et al, 2013Golubović et al, , 2017Golubović et al, , 2018.…”
Section: Study Species and Study Sitesmentioning
confidence: 99%